Development of a Digital Calorimeter Based on Game-Based Learning Interest and Understanding of Types of Heat - Tianita Tianita; Dedy Hamdani; Tiara Hardyanti Utama (IJOEM: Indonesian Journal of E-learning and Multimedia, 2026)
Background: The rapid development of digital technology in education requires innovative laboratory equipment that supports interactive and accurate learning processes. Teaching physics on the topic of specific heat substances still faces challenges, including limited laboratory equipment, low accuracy and precision, and difficulties with analog calorimeters.Aims: This study aims to develop a digital calorimeter based on game-based learning and to analyze its feasibility and effectiveness in improving students’ learning interest and conceptual understanding.Methods: The ADDIE model was used in this study's research and development methodology. Students from SMA Negeri 11 Bengkulu City's Class XI C served as the research subjects. Data were collected through expert validation, sensor performance testing, concept comprehension tests, and a learning interest questionnaire.Result: The research results show that the load cell sensor has a precision error of 0.14% and an accuracy of 0.01%, while the NTC sensor has a precision error and accuracy of 0.19%, thus meeting the experimental measurement requirements. Expert validation yielded a feasibility score of 92.13%, classified as “highly feasible.” The implementation of the learning program demonstrated increases in conceptual understanding (N-Gain of 0.92, high category) and in interest in learning (N-Gain of 0.71, high category).Conclusion: Digital calorimeters are highly suitable for supporting more effective, contextual, and participatory physics learning, and they contribute to the creation of lab resources based on digital technologies that improve the quality of learning and students' active engagement in experimental activities.